A world revision of the Pycnostigminae (Cynipoidea: Figitidae) with descriptions of seven new species - Buffington, M. L.; van Noort, S. (Zootaxa, 2007)
Pycnostigmus rostratus Cameron, 1905, is redescribed and four new species of Pycnostigmus are described: P. mastersonae Buffington & van Noort, new species; P. incognito Buffington & van Noort, new species; P. fossilensis Buffington & van Noort, new species; and P. hoerikwaggoensis Buffington & van Noort, new species. Pycnostigmus mastersonae is the only known species of Cynipoidea with a metallic sheen on the head and mesosoma. A redescription of Tyl osema nigerrimum Kieffer, 1905, is provided as well as the description of two new species: Tylosema dayae Buffington & van Noort, new species and Tylosema ronquisti Buffington & van Noort, new species. The discovery of two new species of Tyl osema in South Africa is noteworthy since the only previously known species, T. nigerrimum Kieffer, is from Algeria. A redescription of Trjapitziniola popovi (Belizin 1951) is provided as well as the description of one new species: Trjapitziniola vanharteni Buffington & van Noort, new species. Trjapitziniola vanharteni was collected in the United Emirates Republic, which extends the distribution of Trjapitziniola well into the Arabian Penninsula. An online key to World species of Pycnostigminae and images are available at www.waspweb.org/Cynipoidea/Figitidae/Pycnostigminae/ index.htm, and images of all species contained within this paper are available from http://morphbank.net.